Hyperbilirubinemia as a diagnostic tool in patients with perforated appendicitis: a prospective study - Gopalreddy, Deepak; Jadhav, Dinesh L.; Kannavar, Sagar (International Surgery Journal, 2020)
Background: This study was conducted to determine the effectiveness of hyperbililrubinemia as diagnostic tool to predict perforated appendicitis. Methods: Patients presenting to department of general surgery of SS Medical College and Hospital during the period from June 2017 to June 2019 with features of appendicitis and liver function tests on admission undergoing laparoscopic or open appendectomy were included in this study. Age, duration of symptoms, temperature, white blood cell counts, bilirubin levels and histological data were collected. Culture and sensitivity of peritoneal fluid was done. Patients were grouped according to histological examination of appendectomy specimens and comparison was made between the groups. Results: The mean bilirubin level of all patients was 0.95 mg/dl (range, 0.1-4.3 mg/dl). The mean bilirubin levels were higher for patients with simple appendicitis compared to those with a non-inflamed appendix (0.8 mg/dl and o.5 mg/dl, p<0.001). Hyperbilirubinaemia had a specificity of 88% and a positive predictive value of 88.89% for acute appendicitis. Patients with appendiceal perforation, however, had a mean bilirubin level of 1.5 mg/dl and were more likely to have hyperbilirubinaemia (p<0.001). The specificity of hyperbilirubinaemia for perforation or gangrene was 70%. Conclusions: patients with hyperbilirubinemia and clinical symptoms of appendicitis should be identified as having a higher probability of appendiceal perforation than those with normal bilirubin levels. Hyperbilirubinemia alone is not a strong enough predictor, but might be more useful when integrated into a scoring system.